NH36 and F3 Antigen-Primed Dendritic Cells Show Preserved Migrating Capabilities and CCR7 Expression and F3 Is Effective in Immunotherapy of Visceral Leishmaniasis - Nico, Dirlei; Martins Almeida, Fernanda; Maria Motta, Juliana; Soares dos Santos Cardoso, Fellipe; Freire-de-Lima, Celio Geraldo; Freire-de-Lima, Leonardo; de Luca, Paula Melo; Maria Blanco Martinez, Ana; Morrot, Alexandre; Palatnik-de-Sousa, Clarisa Beatriz (Frontiers in Immunology, 2018)
Physical contact between DCs and T cell lymphocytes is necessary to trigger the immune cell response. CCL19 and CCL21 chemokines bind to the CCR7 receptor of mature dendritic cells (DCs), and of T cells and regulate DCs migration to the white pulp of the spleen, where they encounter lymphocytes. In visceral leishmaniasis (VL), cellular immunosuppression is mediated by impaired DC migration due to the decreased chemokine secretion by endothelium and to the reduced DCs CCR7 expression. The L. (L.) donovani nucleoside hydrolase NH36 and its C-terminal domain, the F3 peptide are prominent antigens in the generation of preventive immunity to VL. We assessed whether these vaccines could prevent the migrating defect of DCs by restoring the expression of CCR7 receptors. C57Bl6 mice were vaccinated with NH36 and F3 and challenged with L. (L.) infantum chagasi. The F3 vaccine induced a 100% of survival and a long-lasting immune protection with an earlier CD4+Th1 response, with secretion of higher IFN-γ and TNF-α/IL-10 ratios, and higher frequencies of CD4+ T cells secreting IL-2+, TNF-α+ or IFN-γ+, or a combination of two or the three cytokines (IL-2+TNF-α+IFN-γ+). The CD8+ T cell response was promoted earlier by the NH36-vaccine, and later by the F3-vaccine. Maximal number of F3-primed DCs migrated in vitro in response to CCL19 and showed a high expression of CCR7 receptors (26.06 %). Anti-CCR7 antibody treatment inhibited DCs migration in vitro (90 %) and increased parasite load in vivo. When transferred into 28-day-infected mice, only 8 % of DCs from infected, 59 % of DCs from NH36-vaccinated, and 84 % of DCs from F3-vaccinated mice migrated to the white pulp. Consequently, immunotherapy of infected mice with F3-primed DCs only, promoted increases in corporal weight and reductions of spleen and liver parasite loads and relative weights. Our findings indicate that vaccination with F3-vaccine preserves the maturation, migration properties and CCR7 expression of DCs, which are essential processes for the generation of cell-mediated immunity. The F3 vaccine is more potent in reversing the migration defect that occurs in VL and therefore, more efficient in immunotherapy of VL.